δ 18 O sw estimate for Globigerinoides ruber from core-top sediments in the East China Sea - Horikawa, Keiji; Kodaira, Tomohiro; Zhang, Jing; Murayama, Masafumi (BioMed Central Ltd., 2015)
Abstract The paired analyses of the Mg/Ca ratio and oxygen isotopic composition ( δ 18 O c ) of surface-dwelling planktonic foraminifera have become a widely used method for reconstructing the oxygen isotopic composition of ambient seawater ( δ 18 O sw ) as a robust proxy for surface salinity. Globigerinoides ruber ( G. ruber ) is a mixed-layer dweller, and its fossil shell is an ideal archive for recording past sea surface water conditions, such as those caused by variability in the East Asian summer monsoon (EASM). Here, we investigate the validity of shell-derived δ 18 O sw estimates for G. ruber using core-top sediments from the East China Sea (ECS). First, we determined a local δ 18 O sw –salinity equation for the eastern part of the ECS in July [ δ 18 O sw = −7.74 + 0.23 × salinity ]. Then, we calculated δ 18 O sw from core-top δ 18 O c and Mg/Ca values in G. ruber using the δ 18 O c –temperature equation of Bemis et al. (Paleoceanography 13(2):150–160, 1998) and the Mg/Ca–temperature equation of Hastings et al. (EOS 82:PP12B-10, 2001). The core-top δ 18 O sw and salinity were estimated to be in the ranges of −0.2 to +0.39 ‰ and 33.7 to 34.5, respectively, which fall close to the local δ 18 O sw –salinity regression line. The core-top data showed that the Mg/Ca–temperature calibration by Hastings et al. (EOS 82:PP12B-10, 2001) and the δ 18 .